Lateral Crural Repositioning: Implications on Nasal Function - Toriumi, Dean M.; Cristel, Robert T. (Facial Plastic Surgery, 2023)
There are many concepts for surgical management of the nasal tip with varying outcomes on esthetics and nasal function. Nasal tip surgery can influence nasal function based on how the techniques can alter lateral wall integrity. A retrospective chart review of rhinoplasty patients undergoing lateral crural strut grafting (LCSG) with and without repositioning from 2009 to 2017 of the primary author (D.M.T.) was performed. Preoperative and postoperative Nasal Obstruction Symptom Evaluation (NOSE) scores were analyzed. In our study, 832 subjects were evaluated. The mean preoperative NOSE score of all subjects was 35.48. The longest follow-up mean was 652.07 days with a mean NOSE score of 7.07 (p < 0.0001). In the LCSG group, the mean preoperative NOSE score was 22.97. The longest follow-up mean was 583.29 days with a mean NOSE score of 7.22 (p < 0.0001). In the LCSG with repositioning group, the mean preoperative NOSE score was 43.42. The longest follow-up mean was 692.36 days with a mean NOSE score of 7.60 (p < 0.0001). LCSGs with or without repositioning improves nasal function showing significant improvement in NOSE scores. The use of these techniques require adhering to several technical points to maximize outcomes and to avoid deformity.
Keywords: rhinoplasty; lateral crura; lateral crural strut graft; lateral crural repositioning; nasal valve